Characterization Analysis: Cinderella in Grimm's Fairy Tales (Jacob & Wilhelm Grimm) and Cinderella (Grimm's Fairy Tales 2003) - S. Vanya Ides Ramadhani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The present article aims to identify the characterization of Cinderella in two different versions of the fairy tale: "Cinderella Fairy Tales" (Grimm's Fairy Tales Version) by Jacob & Wilhelm Grimm and "Cinderella" (Grimm's Fairy Tales 2003) Selected & Edited by Edna Henry Lee Turpin. By applying a formalist approach, the article focuses solely on identifying the differences in the characterization of the main character between the two fairy tales.Through a close reading method to collect data from both versions, the present paper elaborates on Cinderella's characterization, highlighting her traits such as being good and pious, grateful, resilient, strong and agile, beautiful, dirty, and even a liar. The differences lie in how the authors describe these traits. The characterization of "liar" suggests that Cinderella is not merely an innocent child; she is also capable of engaging in negative behavior.